Meta-analysis and systematic review of coronary vasospasm in ANOCA patients: Prevalence, clinical features and prognosis - Woudstra, Janneke; Vink, Caitlin E. M.; Schipaanboord, Diantha J. M.; Eringa, Etto C.; den Ruijter, Hester M.; Feenstra, Rutger G. T.; Boerhout, Coen K. M.; Beijk, Marcel A. M.; de Waard, Guus A.; Ong, Peter; Seitz, Andreas; Sechtem, Udo; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background: Coronary artery spasm (CAS), encompassing epicardial and microvascular spasm, is increasingly recognized as cause of angina in patients with non-obstructive coronary artery disease (ANOCA). However, various spasm provocation testing protocols and diagnostic criteria are used, making diagnosis and characterization of these patients difficult and interpretation of study results cumbersome. This review provides a structured overview of the prevalence, characterization and prognosis of CAS worldwide in men and women. Methods: A systematic review identifying studies describing ANOCA patients with CAS was performed. Multiple outcomes (prevalence, clinical features, and prognosis) were assessed. Data, except for prognosis were pooled and analysed using random effects meta-analysis models. Results: Twenty-five publications (N=14.554) were included (58.2 years; 44.2% women). Percentages of epicardial constriction to define epicardial spasm ranged from >50% to >90%. Epicardial spasm was prevalent in 43% (range 16-73%), with a higher prevalence in Asian versus Western World population (52% vs. 33%, p=0.014). Microvascular spasm was prevalent in 25% (range 7-39%). Men were more likely to have epicardial spasm (61%), women were more likely to have microvascular spasm (64%). Recurrent angina is frequently reported during follow-up ranging from 10-53%. Conclusion: CAS is highly prevalent in ANOCA patients, where men more often have epicardial spasm, women more often have microvascular spasm. A higher prevalence of epicardial spasm is demonstrated in the Asian population compared to the Western World. The prevalence of CAS is high, emphasizing the use of unambiguous study protocols and diagnostic criteria and highlights the importance of routine evaluation of CAS in men and women with ANOCA.